Studying the Liver Function in Male Neonates of Rats Born to Sertraline-Treated Mothers - Vida Safaei; Mehrdad Shariati (Jurnal Ilmu Ternak dan Veteriner, 2021)
Sertraline is an antidepressant which has toxic effects on the liver. This study was conducted to evaluate the effect of Sertraline administration in pregnancy on liver function of male neonates of rats. Twenty-five pregnant female Wistar rats were divided into 4 groups of 5. The control group did not receive any drug treatments, but experimental (Exp) groups 1, 2 and 3 received 5, 10 and 20 mg/kg Sertraline as gavage throughout the pregnancy, respectively. Twenty-two days after birth, male rats were divided into 4 groups of 10 based on the previous division and after weighing, by taking blood directly from the heart, serum levels of Alanine transaminase (Alt), Aspartate transaminase (AST), Alkaline phosphatase (Alp), Albumin (Alb), Total protein (TP), and Bilirubin (Bili) were measured and the liver tissue was also analyzed histopathologically after weighing. In Exp groups, a significant decrease in body weight, TP and Alb serum levels were observed compared to the control group (p<0.05). In Exp group 3, a significant decrease in liver weight was observed compared to the control group (p˂0.05). In Exp groups 2 and 3, a significant increase in serum levels of Alp, Alt and Bili in was observed compared to the control group (p˂0.05). A significant increase in AST serum level was observed in Exp groups compared to the control group (p˂0.05). Liver tissue destruction was observed in all 3 Exp groups. The administration of Sertraline in pregnant female rats causes liver damage and increases liver enzymes and blood biochemical parameters in their male offspring.